Trace Pt Clusters Dispersed on SAPO‐11 Promoting the Synergy of Metal Sites with Acid Sites for High‐Effective Hydroisomerization of n‐Alkanes. Issue 5 (4th February 2019) - Wang, Dongxu; Liu, Jiancong; Cheng, Xusheng; Kang, Xin; Wu, Aiping; Tian, Chungui; Fu, Honggang
Abstract: The significant increase of catalytic efficiency while remaining low Pt usage is constantly pursued, but remains a challenge. Here, a "vacuum‐assisted" (VA) process toward Pt clusters dispersed on SAPO‐11 (S‐11) is shown for a high‐effective hydroisomerization of n ‐C16 . The VA can make effective trapping of the Pt precursor on S‐11 due to intensive capillary action, being conductive to stabilize and disperse Pt cluster (≈1 nm) on S‐11 (V‐Pt/S‐11) for promoting synergy of Pt sites and acid sites on S‐11. The test indicates excellent catalytic activity and stability of trace Pt clusters (0.15 wt%, even lower, 0.035 wt%) on S‐11 (≈94.4% isomer selectivity at 94.3% conversion), much superior to I‐0.15 wt% Pt/S‐11 from traditional impregnation routes (≈88% selectivity at 90% conversion) and ever reported catalysts. The V‐Pt/S‐11 is also superior for the hydroisomerization of catalytic diesel oil with a decrease of freezing point up to 40 °C after hydroisomerization. The superior performance is attributed to the exposure of high acid density due to little coverage of Pt cluster on S‐11, high dispersion of Pt leading to form more metal–acid bifunctional sites, and enhanced (de)hydrogenation ability of Pt clusters. All of them can promote the effective synergy of metal sites (Pt) and acid sites. Abstract : Trace, well‐dispersed Pt clusters are anchored on SAPO‐11(S‐11) based on a robust "vacuum‐assisted" process. The catalyst shows superior performance for the hydroisomerization of n ‐hexadecane and catalytic diesel oil with high yields of isomers, superior to catalysts ever reported. The superior performance is attributed to small size and good dispersion of Pt on S‐11 for effective synergy of metal and acid sites.